Аналіз можливого впливу пружних деформацій на властивості акустоелектронних пристроїв на ПАХ - Мельничук, Андрій (Видавництво Національного університету «Львівська політехніка», 2009)
In this paper the argumentation of appropriateness of research and analysis of possible elastic deformation affect on surface acoustic wave devices characteristics is described.
Keywords: surface acoustic wave; elastic deformation; strain